A Simplified Calculation Method of Length Adjustment of Datum Strand for the Main Cable with Small Sag. (22nd January 2019) - He, Jun; Li, Chuanxi; Ke, Hongjun; Liu, Yang; Zhang, Yuping; Dong, Chuangwen; Li, Hongli; Zhang, Zhe
Abstract : In order to overcome the complicated iterative process of the cable length adjustment based on catenary theory and large error of length adjustment for cable with a small sag based on the parabola theory, this paper firstly develops a direct and simply calculation method based on parabola theory, considering the influence of elastic elongation on the cable unstressed length, which can apply for datum strand of the main cable and catwalk bearing rope with a small sag to improve the construction accuracy of the datum strand of suspension bridges. Then, the applicability of the proposed cable length adjustment formula under different conditions of the sag-span ratio is analyzed and compared with other calculation methods based on the theory of catenary or parabola. Finally, numerical examples are presented and discussed to illustrate the accuracy and efficiency of the proposed analytical method.